Identification of a New Genotype of African Swine Fever Virus in Domestic Pigs from Ethiopia. Issue 5 (22nd May 2016) - Achenbach, J. E.; Gallardo, C.; Nieto‐Pelegrín, E.; Rivera‐Arroyo, B.; Degefa‐Negi, T.; Arias, M.; Jenberie, S.; Mulisa, D. D.; Gizaw, D.; Gelaye, E.; Chibssa, T. R.; Belaye, A.; et al.
Summary: African swine fever (ASF) is an important emerging transboundary animal disease (TAD), which currently has an impact on many countries in Africa, Eastern Europe, the Caucasus and the Russian Federation. The current situation in Europe shows the ability of the virus to rapidly spread, which stands to threaten the global swine industry. At present, there is no viable vaccine to minimize spread of the disease and stamping out is the main source of control. In February 2011, Ethiopia had reported its first suspected outbreaks of ASF. Genomic analyses of the collected ASF virus (ASFV) strains were undertaken using 23 tissue samples collected from domestic swine in Ethiopia from 2011 to 2014. The analysis of Ethiopian ASFVs partial p72 gene sequence showed the identification of a new genotype, genotype XXIII, that shares a common ancestor with genotypes IX and X, which comprise isolates circulating in Eastern African countries and the Republic of Congo. Analysis of the p54 gene also followed the p72 pattern and the deduced amino acid sequence of the central variable region (CVR) of the B602L gene showed novel tetramer repeats not previously characterized.